Thermal activation in the Zr65Cu18Ni7Al10 metallic glass by creep deformation and stress relaxation. (1st March 2016) - Zhang, C.; Qiao, J.C.; Pelletier, J.M.; Yao, Y.
Abstract: In the current study, jump stress creep and stress relaxation experiments were performed to Zr65 Cu18 Ni7 Al10 metallic glass below the transition temperatures Tg. The viscoplasticity effect and transition between the Newtonian and non-Newtonian flow are investigated. The activation energy of creep is obtained from two theoretical methods. It is found that the activation volume of creep is more than that of stress relaxation, which is mainly caused by different organizational behaviors. Graphical abstract: